Effects of resolution in real and reciprocal spaces from a 2D detector at a high-energy synchrotron beamline. Issue 1 (2nd January 2018) - Bernasconi, Andrea; Wright, Jonathan
Abstract : Different experimental conditions at a versatile high-energy beamline equipped with a two-dimensional detector have been compared for powder diffraction and pair distribution function (PDF) experiments. In particular, sample size and sample to detector distances have been evaluated on a standard sample, to evaluate their effects in both Q and real space. Two illustrative cases are also discussed. The average structure and local distortions in a BaTiO3 powder with 100 nm particle size show that spurious ripples in the PDF are suppressed by increased counting statistics. Effects of small amounts of a crystalline impurity phase on a SiO2 .Al2 O3 .Na2 O.CaO glass have been quantified.